Combined genome-wide association analysis and transcriptome sequencing to identify candidate genes for flax seed fatty acid metabolism. (September 2019) - Xie, Dongwei; Dai, Zhigang; Yang, Zemao; Tang, Qing; Deng, Canhui; Xu, Ying; Wang, Jing; Chen, Jing; Zhao, Debao; Zhang, Shuli; Zhang, Shuquan; Su, Jianguang
Highlights: A combination of GWAS and RNA-seq analyses identified candidate genes related to flax fatty acids. The temporal expression of candidate genes related to fatty acid synthesis during the development of flax seeds was studied. In addition, the correlation between candidate genes and fatty acid components at different developmental stages was analyzed to explore the effects of candidate genes in the process of fatty acid metabolism and accumulation. Abstract: Flax seeds have a high oil content and are rich in unsaturated fatty acids, which have advantageous effects in preventing chronic diseases, such as cardiovascular diseases. At present, flax seeds are mainly developed for oil. Therefore, it is of practical significance to identify the candidate genes of fatty acid metabolism in flax seeds for breeding flax seeds with high oil content. In the present study, a natural population of flax containing 224 samples planted in 3 different environments was studied. The genome-wide association analysis (GWAS) of seed fatty acid content was conducted based on specific length amplified fragment sequencing (SLAF-seq) data. Transcriptome sequencing (RNA-seq) of samples from 3 different periods (14 d, 21 d and 28 d after anthesis) during seed development of the low oil variety Shuangya 4 and the high oil variety NEW was performed. The candidate genes for seed fatty acid metabolism were identified by combined analysis of these 2 methods. GWAS detected 16 SNP loci significantly associated with seed fatty acid content, and RNA-seq analysis identified 11, 802 differentially expressed genes between high and low oil samples. Pathway enrichment analysis revealed that some differentially expressed genes were classified into fatty acid-related pathways. After comparison of these differentially expressed genes with the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, 20 genes homologous to other species were obtained. After analysis, 10 candidate genes were screened by GWAS and RNA-seq screening. Of these 10 genes, qRT-PCR assays using flax seeds in 5 different developmental stages showed that the expression levels of 6 candidate genes were significantly correlated with 5 fatty acid contents in seeds of the high oil variety NEW. Through metabolic pathway analysis found that 6 genes were involved in important fatty acid metabolic pathways, and some of them also have upstream and downstream regulation relations. The present study combined GWAS and RNA-seq methods to identify candidate genes for fatty acid metabolism in flax seeds, which provided reference for screening of candidate genes with complex traits.